Peroxidase application reduces microcrystalline cellulose recalcitrance towards cellulase hydrolysis in model cellulose substrates and rooibos biomass - Mohotloane, Mamosela Marriam; Alexander, Orbett; Adoons, Vanthini Nelson; Pletschke, Brett Ivan; Mafa, Mpho Stephen (Elsevier, 2024)
We have identified a HRP enzyme with microcrystalline cellulose activity, which has not yet been explored. The current study investigated the effect of HRP pretreatment on the microcrystalline cellulose substrates, Avicel and filter paper. SEM findings showed that HRP pretreatment catalysed the para-microcrystalline regions of Avicel, cracking and opening the pores on the surface. On filter paper, HRP removed the para-microcrystalline regions exposing fibres. Crystallinity index (CrI) analysis confirmed that HRP increased the CrI of Avicel from 49 % to 54.19 % and filter paper from 42 % to 47 %. The cellulose crystallite sizes increased from 45 to 47 nm at the 002 lattices in Avicel, suggesting a reduction of crystalline cellulose. In addition, endoglucanase displayed 1.15-fold increased activity on HRP-pretreated Avicel, confirming reduced crystalline cellulose. These findings showed that HRP pretreatment changed the structural and chemical properties of Avicel, i.e., loosening crystalline cellulose to make the substrate accessible to enzymes during hydrolysis. Finally, these findings were supported by rooibos microcrystalline cellulose modification post-HRP pretreatment, resulting in a 95 % yield of soluble sugars at 25 mg enzyme cocktail/g biomass.
Keywords: cellulose; microcrystalline cellulose; horseradish peroxidase; biomass pretreatment; endoglucanase; enzyme cocktail